Ethics of Qualitative Research – Selected Aspects - Mazurek, Emilia (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
Every scientific study, regardless of the discipline in which it is conducted and theresearch methodology, is embedded in the axiological dimension. Therefore, the researcher,already at the stage of creating the research concept, and later during its implementation andpublication of the obtained results, makes many ethical choices for which they are responsible.The aim of the chapter is to present selected issues concerning the ethics of qualitativeresearch, with particular emphasis on research conducted on the basis of andragogy. Thechapter discusses significant aspects of ethical correctness in scientific research, taking intoaccount the perspective of the research participant and the perspective of the researcher, aswell as the phenomenon of whistleblowing in the academic environment and doubts relatedto it. It emphasizes that all persons and entities involved to some extent in scientific research(including: participants, researchers, recipients of research reports, scientific councils, editorialboards, institutions financing scientific research, publishers) are exposed to ethicallyunfavorable actions of the researcher and/or the applied research procedure. The most importantprinciples and postulates regarding research ethics contained in professional codesof scientists and guides in the field of research ethics as well as examples from researchprojects were indicated, while noting that they are only certain guideposts, but researchersare obliged to make decisions in their research practice with a sense of responsibility forothers and themselves.